Analysis Relationship of The Current Velocity and Primary Productivity on Coral Reef in Bama Beach - Paluphi, Raut Wahyuning; Widhi, Raut Nugrahening; Azis, Muh. Aksa (Jurnal Biologi Tropis, 2025)
Coral reefs are one of the ecosystems with the highest biodiversity. The purpose of this study was to determine the relationship of current velocity has on primary productivity in coral reef ecosystems. Current velocity measurements using a current meter and primary productivity measurements using the Winkler method by ƒincubated for 5 hours. The results obtained from this study are that current velocity has an effect on primary productivity in coral reef ecosystems, R value 0.895 and R Square shows 80.1%. The significance value obtained Sig = 0,04, which means less than 0.05, it can be interpreted that the effect of current velocity on primary productivity is strong category. Based on the study results obtained, more research is necessary to find out how much the velocity of the current affects the primary productivity of the coral reef.